Roland Barthes, Autonimic Writer (2022)
In Barthes, criticism rushes into a form of literature. What does his criticism as literature consist of? What relationship, of similarity and difference, does it have with the impressionism of Jules Lemaitre and Anatole France? This essay aims to investigate criticism as literature that appears in the work of Barthes. To do this, starting from a contrast between the first and the last of his texts, I will analyze some topics of impressionist criticism that reappear in Barthes, such as subjectivism, reading and rhetoric. I will seek to develop the hypothesis according to which the Barthesian work is an attempt to make criticism a form of literature in the Impressionist tradition, but according to a singular appropriation traversed by linguistics and psychoanalysis. Therefore, I will try to develop and establish the foundation of what Barthes has called autonimic writing.